Decoction derived from Allium ascalonicum L. bulbs and Sojae Semen Praeparatum alleviates wind-cold-type common cold via Nrf2/HO-1 pathway and modulation of Lactobacillus murinus level - Jiang, Yuanyuan; Wei, Wenfeng; Zhou, Jiaxin; Qiu, Shixian; Yang, Qixin; Huo, Jin hai; Wang, Weiming (Frontiers in Pharmacology, 2024)
Background: Cong-Chi decoction (CCD) is composed of Allium ascalonicum L. (shallot) bulbs and Sojae Semen Praeparatum. Both botanical drugs are utilized regularly in traditional Chinese medicine. However, no recent pharmacological studies investigating their synergistic effects have been published. Despite their roles in the treatment of the common cold for thousands of years, their pharmacological mechanisms of action against wind-cold, a type of common cold, have yet to be comprehensively explored.Methods: A mouse model was standardized using wind-cold modeling equipment. The antiinflammatory, antioxidant, and anti-apoptotic effects of CCD were then studied. 16S rRNA sequencing was employed to analyze the association between Lactobacillus murinus and changes in body temperature. Additionally, the antipyretic effects of L. murinus were validated via animal experiments.Our results indicated that CCD improved the symptoms of wind-cold by decreasing fever, reducing the levels of pro-inflammatory factors, decreasing cellular apoptosis, and increasing the blood leukocyte count and the number of lymphocytes, thereby alleviating lung tissue damage. The effects of CCD were mediated by upregulation of pulmonary Nrf2 and HO-1 expression, thereby reducing oxidative damage in the lungs, in addition to other anti-inflammatory mechanisms. Further, CCD increased the abundance of L. murinus in the intestinal tract. Animal experiments confirmed that L. murinus ameliorated fever in mice.Conclusions: CCD exhibited remarkable antioxidant and anti-inflammatory properties for the effective treatment of wind-cold type common cold. Further, its regulatory effects on L. murinus represent a novel mechanism for product development.